Produktivitas Kerja Karyawan Berbasis Motivasi, Disiplin Kerja dan Lingkungan Kerja - Asep Awaludin; Tini Kartini; Palahudin Palahudin (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the influence of motivation, work discipline, and work environment of employees in the production department of PT Dobha Putra Salim. The research method used is a quantitative method with a survey approach. Data were collected through questionnaires distributed to 122 respondents who were employees of the production department of PT Dobha Putra Salim. The data analysis techniques used were multiple linear regression, multiple correlation coefficient, determination coefficient, F test and t test. The results of the correlation analysis showed that the R value was 0.938, meaning that each variable had a very strong relationship. While the determination coefficient (R Square) showed the influence of motivation, work discipline, and work environment on employee work productivity in the production department of PT Dobha Putra Salim by 88.1% while the remaining 11.9% was explained by other variables not included in this study. The results of the F test and t test showed that simultaneously and partially motivation, work discipline, and work environment had a positive and significant effect on work productivity at PT Dobha Putra Salim